Teachers' Attitudes Towards Mainstreaming of Blind Students with the Ordinary Students' Classes in Public Schools in Sahab District and its relation with Some Variables - Hasan Al-Omari; Rehab Shaalan (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to figure out the attitudes of teachers towards integrating the blind students into the classes of the ordinary students in the public schools of Sahab and its relation with some variables. The study adopted the questionnaire for data collection from the sample members. The study sample consisted of (140) male and female teachers in Sahab's public schools who were randomly selected from the study population. The study concluded that the teachers' attitudes towards the mainstreaming of blind students in the ordinary students' classes were positive in all the (cognitive, social, emotional and academic) dimensions of the study. The study also concluded that there were statistically significant differences at sig. (α =0.05) in the teachers' attitudes towards integrating of the blind students in the ordinary students' classes were in favor of males, statistically significant differences at sig. (α =0.05) in the opinions of the sample members on the academic and cognitive dimensions in favor of the diploma holders, no statistically significant differences at sig. (α =0.05) in the opinions of the sample members on the social and emotional dimensions according to the variable of the scientific qualification, no statistically significant differences at sig. (α =0.05) in the teachers' attitudes towards integrating the blind students in the ordinary students' classes according to the variable of the number of years of service, and finally no difference in the responses of the teachers towards the integrating of the blind students into the ordinary students' classes according to teaching blind students.